Implementasi Sistem Informasi Rumah Sakit sebagai Inovasi Tata Kelola Pelayanan Publik di RSUD Toto Kabila Bone Bolango - Desi Novitasari; Yolanda Ngabito (YASIN, 2026)
Although the implementation of the Hospital Information System (SIRS) has received attention in various previous studies, studies that specifically discuss the role of SIRS as an innovation in public service governance at regional hospitals remain limited. This study aims to analyze the implementation of SIRS as an innovation in public service governance at RSUD Toto Kabila, Bone Bolango Regency. This study used a qualitative approach with a case study design, involving one key informant selected through purposive sampling, namely the person responsible for implementing SIRS at RSUD Toto Kabila. Data were collected through structured interviews, direct observation, and documentation studies, and were then analyzed using thematic analysis. The results show that the implementation of SIRS at RSUD Toto Kabila has generally been effective in supporting hospital reporting and information management. System implementation is supported by adequate technological infrastructure, strong leadership commitment, and good interunit coordination. However, its implementation still faces obstacles in the form of limited human resources, data input processes that remain manual, the absence of specific standard operating procedures, dependence on a central server, and the suboptimal implementation of routine internal evaluation. The conclusion of this study affirms that optimizing SIRS requires strengthening human resources, system integration, clear governance mechanisms, and continuous evaluation. The implications of this study contribute to the development of studies on public service governance and digital transformation in the health sector, while also providing practical input for hospital management and policymakers in improving the effectiveness of health information systems in regional hospitals.